Campaign Questions and Answers guide
This document provides campaign guidance on handling question-and-answer sessions at public events. It advises candidates to restate questions for clarity, compliment questioners, pause before answering, and tailor responses to audience attitudes while remaining principled. The notes stress giving concise, memorable answers, reframing difficult or emotionally charged questions, and acknowledging complexity when necessary. It also recommends preparing "icebreaker" questions, managing dominant audience members diplomatically, and closing by thanking attendees for their participation.